2023
DOI: 10.3758/s13414-023-02679-4
|View full text |Cite
|
Sign up to set email alerts
|

A novel end-to-end dual-camera system for eye gaze synchrony assessment in face-to-face interaction

Abstract: Quantification of face-to-face interaction can provide highly relevant information in cognitive and psychological science research. Current commercial glint-dependent solutions suffer from several disadvantages and limitations when applied in face-to-face interaction, including data loss, parallax errors, the inconvenience and distracting effect of wearables, and/or the need for several cameras to capture each person. Here we present a novel eye-tracking solution, consisting of a dual-camera system used in con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…We have recently shown that an adaptation of current deep-learning methodologies for eye tracking 48 , 49 , together with a dual-camera system, can determine gaze to discriminate specific facial areas and quantify movement synchronization 42 . The camera system has been developed with neurodevelopmental disorders in mind; it is minimal, does not include any wearables, such as eye-tracking glasses, and is located on a table between two individuals without covering the face of the person in front of them, see Fig.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…We have recently shown that an adaptation of current deep-learning methodologies for eye tracking 48 , 49 , together with a dual-camera system, can determine gaze to discriminate specific facial areas and quantify movement synchronization 42 . The camera system has been developed with neurodevelopmental disorders in mind; it is minimal, does not include any wearables, such as eye-tracking glasses, and is located on a table between two individuals without covering the face of the person in front of them, see Fig.…”
Section: Methodsmentioning
confidence: 99%
“…This error was lower error than in the previous implementation of the camera system, indicating the value of individual deep-learning calibration to actual face-to-face gaze. More detailed information about the eye-tracking technique can be found in Thorsson et al 42 . Missing data were defined as gaze that could not be estimated, and represented about 10.3% of the data collected in the experiment.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations